Learner Autonomy, Motivation and English Speaking Proficiency: A Study Among English Foreign Language Univerity Students in Nghe An - Minh, Nguyen Hoang; Ngoc, Nguyen Thi Duong (VNU Journal of Science: Education Research; Vol 39 No 1DO - 10.25073/2588-1159/vnuer.4700, 2023)
It is well acknowledged that autonomy and motivation have significant effects on language acquisition performance. Despite considerable work on motivation and autonomy in language learning, the relationship between learners' autonomy, motivation, and English speaking proficiency has not been sufficiently investigated. This article aims to explore the link between learners' autonomy, motivation, and English speaking proficiency. 200 English Foreign Language university students at Vinh university were given questionnaires to assess their autonomy and motivation in developing speaking abilities. The association between learners' autonomy, motivation, and their English speaking proficiency was determined by comparing this data to the speaking proficiency test scores. The analysis of the acquired findings revealed that learners with lower speaking grades reported being less independent than those with better English speaking proficiency. Similarly, the results indicated a correlation between learners' speaking grades and motivation levels. Some pedagogical implications thus should entail modifications to the language instruction curriculum to facilitate the development of learner autonomy and motivation.